EFFECT OF SHOE RAISE ALONG WITH MOTOR RELEARNING PROGRAMME (MRP) ON AMBULATION IN CHRONIC STROKE (International Journal of Physiotherapy, 2016)
Background: Stroke subjects face reduced tolerance to activity and sedentary lifestyle due to various impairments, such as muscle weakness, pain, spasticity, and poor balance. Thus, loss of independent ambulation especially outdoors is generally observed in them.Methods: Chronic stroke patients (> 6 months) with Functional Ambulation Category score > 2 and able to walk at least 10 meters of distance with and without assistance from a tertiary healthcare centre were selected and treated. Subjects were randomly divided into 2 groups control group (n=14) and experimental group (n=13). Each group received Motor Relearning Programme for 60 minutes, 6 times a week for 4 weeks. The experimental group received an additional shoe-raise of 1 cm on the unaffected side along with while ambulating during therapy as well as at home. Pre and post treatment the patients were assessed for spatio-temporal parameters using foot print analysis method and Rivermead Visual Gait Assessment (RVGA) Score using RVGA scale.Results: There was significant improvement seen in almost all the spatio-temporal gait parameters and RVGA score in within group analysis. Whereas on between group the results from between group comparison suggests that subjects in MRP with shoe-raise group showed better results in spatio-temporal parameters of gait than subjects receiving MRPalone. But there was no additional benefit of shoe-raise seen on RGVA score and angle of toe-out parameter.Conclusion: Additional use of shoe-raise helps to improve spatio-temporal gait parameters. However, there was no additional change seen in RVGA score.